Fast charge separation and transfer strategy in polymeric carbon nitride for efficient photocatalytic H2 evolution: Coupling surface Schottky junctions and interlayer charge transfer channels. (1st December 2022) - Gao, Manyi; Tian, Fenyang; Zhang, Xin; Liu, Yequn; Chen, Zhaoyu; Yu, Yongsheng; Yang, Weiwei; Hou, Yanglong
Abstract: Reinforcing the charge separation and transfer in layered polymeric carbon nitride (PCN) is the key issue to enhance its photocatalytic activity but still remains very challenging. Herein, for the first time, the synergetic Pd single atoms (PdSAs) and carbon-supported Pd nanoparticles (NPs) are introduced into the interlayer and surface of layered PCN respectively to address this challenge. The PdSAs are in intimate contact with the adjacent PCN layers and serve as interlayer charge transfer channels, while the carbon-supported Pd NPs contribute to multistep PCN-carbon-Pd NPs Schottky junctions on PCN surface. Experiments and theoretical calculations demonstrate that such unique architectures provide intrinsic driving force to extract the electrons from PCN to outermost Pd NPs with high migration rate via vertical PdSAs channels. This directional charge transfer in PCN greatly expedite the separation of charge carriers in both inner and surface of PCN and simultaneously yield electron-rich Pd NPs active sites with optimized H2 adsorption energy, thus leading to improved intrinsic H2 evolution reaction kinetics. Consequently, the Pd/PCN2 performs ultrahigh photocatalytic H2 evolution rate of 83.34 mmol g −1 h −1 in the dispersed particulate system and 100.4 mmol h −1 m −2 in the film form under simulated sunlight. This work provides a new promising approach to engineer the spatial charge transfer behaviors for high-performance PCN-based photocatalysts. Graphical Abstract: The vertical PdSAs charge transfer channels and multistep PCN-carbon-Pd NPs Schottky junctions are introduced into the interlayer and surface of layered PCN, respectively, which can engineer the spatial charge transfer behaviors and achieve fast charge separation and transfer, thus promoting photocatalytic water-splitting to H2 with the rate of 83.34 mmol g −1 h −1 . ga1 Highlights: Surface schottky junctions and interlayer charge transfer channels are introduced into the PCN to engineer the spatial charge transfer behaviors. The surface PCN-C-Pd Schottky junctions harness electrons from PCN to outermost Pd NPs. The interlayer PdSAs channels greatly elevates the vertical electron mobility. The two synergetic components greatly expedite the separation/transfer of charge carriers. The Pd/PCN2 performs ultrahigh photocatalytic H2 evolution rate of 83.34 mmol g −1 h −1 in the dispersed particulate system and 100.4 mmol h −1 m −2 in the film form.